The Effectiveness of the SIRI Model (Stimulation, Investigation, Review, and Inference) on Problem-Solving Skills in Environmental Change Material Integrated with Islamic Values - Sylvia Nurazizah; Asrianty Mas’ud; Iwan Ridwan Yusup (Journal of Educational Sciences, 2026)
Students’ problem-solving skills particularly regarding environmental change still need improvement and have not yet been integrated with Islamic values. This study aims to analyze the effectiveness of the SIRI (Stimulation, Investigation, Review, and Inference) learning model on problem-solving skills in environmental change lessons integrated with Islamic values. This study employed a quantitative approach using a quasi-experimental method and a Non-equivalent Control Group Design. The sample consisted of 92 10th-grade students at a high school in Bandung, selected using purposive sampling. Data were collected through observation sheets and an essay test on problem-solving skills integrated with Islamic values. The observation results showed that the implementation of instruction in the experimental and control classes fell into the “very good” category, with percentages of 93% and 92%, respectively. The average N-Gain for the experimental class (0.60) was higher than that of the control class (0.47). Hypothesis testing showed a Sig. (2-tailed) value < 0.05 with a Cohen’s d value of 1.024 (large effect). Thus, the SIRI model is effective in improving students’ problem-solving skills.